Molecular Mechanism Associated With the Impact of Methane/Oxygen Gas Supply Ratios on Cell Growth of Methylomicrobium buryatense 5GB1 Through RNA-Seq - Hu, Lizhen; Yang, Yongfu; Yan, Xin; Zhang, Tianqing; Xiang, Jing; Gao, Zixi; Chen, Yunhao; Yang, Shihui; Fei, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
The methane (CH4)/oxygen (O2) gas supply ratios significantly affect the cell growth and metabolic pathways of aerobic obligate methanotrophs. However, few studies have explored the CH4/O2 ratios of the inlet gas, especially for the CH4 concentrations within the explosion range (5∼15% of CH4 in air). This study thoroughly investigated the molecular mechanisms associated with the impact of different CH4/O2 ratios on cell growth of a model type I methanotroph Methylomicrobium buryatense 5GB1 cultured at five different CH4/O2 supply molar ratios from 0.28 to 5.24, corresponding to CH4 content in gas mixture from 5% to 50%, using RNA-Seq transcriptomics approach. In the batch cultivation, the highest growth rate of 0.287 h–1 was achieved when the CH4/O2 supply molar ratio was 0.93 (15% CH4 in air), and it is crucial to keep the availability of carbon and oxygen levels balanced for optimal growth. At this ratio, genes related to methane metabolism, phosphate uptake system, and nitrogen fixation were significantly upregulated. The results indicated that the optimal CH4/O2 ratio prompted cell growth by increasing genes involved in metabolic pathways of carbon, nitrogen and phosphate utilization in M. buryatense 5GB1. Our findings provided an effective gas supply strategy for methanotrophs, which could enhance the production of key intermediates and enzymes to improve the performance of bioconversion processes using CH4 as the only carbon and energy source. This research also helps identify genes associated with the optimal CH4/O2 ratio for balancing energy metabolism and carbon flux, which could be candidate targets for future metabolic engineering practice.